1977
DOI: 10.1002/polc.5070580125
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of supermolecular structure of polyimides and polyester imides

Abstract: SYNOPSISSupermolecular structures of fourteen heterocyclic thermally stable polymers of the polyimide (PI) and polyesterimide (PEI) class have been investigated by X-ray scattering, optical, dilatometric and thermomechanical methods. Quasi-crystalline structure of these polymers in the initial amorphous state of poly(amic acid) and poly(ester amic acid) and also after chemical imidization has been revealed. The quasi-crystalline structure is characterized by a biaxial polarizability ellipsoid with a negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…As stated in the Introduction, the insight into the PVT behaviors of crystalline PIs is valuable to predict the responses to pressures and temperatures of PIs and to investigate the limiting values of compressibility and thermal expansion coefficients of PIs. Because all the PIs prepared in this study were reported to form crystalline structures based on the orthorhombic unit cell, 6 the volumetric variations at elevated pressures in the ordered region were calculated as a summation of the variations in the lattice parameters along the a-, b-, and c-axes. Figure 9 shows the volumetric variations in the ordered region of the PMDA/ PPD, PMDA/DATP, and PMDA/ODA powders.…”
Section: Macromoleculesmentioning
confidence: 99%
“…As stated in the Introduction, the insight into the PVT behaviors of crystalline PIs is valuable to predict the responses to pressures and temperatures of PIs and to investigate the limiting values of compressibility and thermal expansion coefficients of PIs. Because all the PIs prepared in this study were reported to form crystalline structures based on the orthorhombic unit cell, 6 the volumetric variations at elevated pressures in the ordered region were calculated as a summation of the variations in the lattice parameters along the a-, b-, and c-axes. Figure 9 shows the volumetric variations in the ordered region of the PMDA/ PPD, PMDA/DATP, and PMDA/ODA powders.…”
Section: Macromoleculesmentioning
confidence: 99%
“…The crystal structure of PMDA-ODA has been reported in the literature by several groups. [8][9][10][11][12] All studies indicate that the chain forms a planar zigzag (2/1 helix) conformation and that the c-axis is perpendicular to the a-b plane (Figure 1). However there are significant variations in the dimensions of a and b and in the number of chains per unit cell (1 or 2 chains/cell), and the angle between the aand b-axes is determined to be either 90°or 100°.…”
Section: Resultsmentioning
confidence: 99%
“…However there are significant variations in the dimensions of a and b and in the number of chains per unit cell (1 or 2 chains/cell), and the angle between the aand b-axes is determined to be either 90°or 100°. 11 Since the periodicity of the PMDA-ODA chain is dependent on the curing process, as apparent in the literature, [8][9][10][11][12] it is also reasonable to expect variations in the lateral dimensions. Furthermore, the limited number and large breadth of overlapping reflections (at least in the bulk samples) can partially explain the discrepancies in the unit cell structure determination.…”
Section: Resultsmentioning
confidence: 99%
“…The indexing of the WAXS pattern reported for PMDA-ODA indicates either an orthorhombic [15,16] or monoclinic [17] structure with one chain per unit cell. However, a crystal structure calculation which allows for perturbations in the chain conformation and interchain differences indicates that two chains per lattice cell is more suitable [18], and our indexing is based on the latter structure.…”
Section: Effect Of Polyimide Morpliology and Topography On Adhesionmentioning
confidence: 99%